(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The study approaches to explore tertiary level students’ perceptions of Using Facebook for Language Learning. Social networking sites are believed to be good aid for learning language projecting content and language skills and there has been a number of studies on this issue. Like other social networking Sites Facebook can be a platform for learning English. Earlier several studies have discovered that students of tertiary level do not have good command in using English even though, this population spent much time on Facebook interacting with friends, sharing and expressing their ideas, opinion, photos and so on. While using Facebook the tertiary level students, to great extent, use English and thus, this population might have thoughts about what certainty and what problems they face on Facebook using English. The study was conducted with a quantitative approach where data has been collected through a cross sectional survey from purposively selected 100 tertiary level students with a structured questionnaire used as a tool. The findings of the study present that the students are positive to think Facebook as a language learning platform even though they addressed some language and technological challenges. Although the area of the study is small, the result of the t-test shows that the total population might have the same opinion as the sample group. Teacher’s World: Journal of Education and Research, 49 (1), 117-136